The law of oil concessions in the Middle East and North Africa - Cattan, Henry; Reese, Willis L. M.; Parker School of Foreign and Comparative Law. (Dobbs Ferry, N.Y. : Oceana Publications, 1967)
This book represents a useful contribution to the development of the law of oil concessions and other State contracts and should prove of material assistance to practicing attorneys, legal scholars and political scientists, as well as to those officials of Government and oil companies whose work involve oil concessions.
"Published for the Parker School of Foreign and Comparative Law."
Includes bibliographical references and index.
rpm 23/01/2019
Loans
Keywords: Oil and gas leases